The Effectiveness of Tamarindus indica Extract in Total Osteoblast Cell of Male Wistar Rat’s Femur Bone Induced by Aluminium - Indah Pratiwi; Rena Normasari; Rony Prasetyo (Faculty of Medicine, University of Jember, 2020)
Aluminum is widely used in life but includes non-essential metals toxic to the human body that most accumulates in the femur. Aluminum is toxic because it increases the number of free radicals resulting in oxidative stress that causes osteoblast apoptosis. Tamarindus indica has the most potent antioxidant effect on the seed. The polyphenol content in Tamarindus indica seed are myricetin, procyanidin B2, and caffeic acid. Antioxidants in Tamarindus indica seed have mechanism of donating electrons from the -OH group in the phenolic ring to stop oxidative chain reactions and prevent the formation of hydroxyl radicals and lipid peroxidation that play a role in cell apoptosis. The purpose of this study to determine the effect of giving Tamarindus indica extract on the total osteoblasts of femur bone in male wistar rats induced by aluminum. This research is a true experimental in vivo with randomized post-test only control group design using 25 male Wistar rats divided into five groups. Aluminum is given orally dose 300mg/kgBB and Tamarindus indica extract dose 25, 50, 100mg/kgBB for 10 weeks. The results of this study indicate the average total of osteoblasts in groups K, P1, P2, P3, P4 are 15.21 ± 1.71; 18.48 ± 3.65; 17.8 ± 7.05; 17.13 ± 1.16; 16.74 ± 5.71. Data analysis used the Kruskal Wallis test. The results of data analysis showed that there was no significant differences in all groups (p = 0.581). Based on the results of this study, Tamarindus indica extract that was given to male wistar rats induced by aluminum for 10 weeks had no effect on the total osteoblasts.